(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
Given the outstanding importance bestowed on rhetoric and persuasive strategies as they are critical in many spheres, among them politics, this article came to analyze political discourse applying an innovative rhetorical framework that draws on the Burkean cluster analysis to answer the following question: what are the persuasive strategies employed by Barack Obama in his last electoral campaign? The data are comprised of the last campaign speech Obama delivered in 2012. The contribution of this research lies in: (i) providing an answer(s) to the research question and (ii) suggesting an inductive perspective to carry out rhetorical analyses. The results proved the efficiency of the suggested method as it permitted the identification of a combination of tactics Obama utilized. They are: emotional arousals, credibility, attack, and metaphor - albeit the existence of a heavy reliance on pathos. Key terms - rhetorical analysis, persuasive strategies, political discourse, inductive analysis, Barack Obama.